Politisierung zwischen den Zeilen. Betrachtungen zum politisierenden Charakter der Schreibweisen von Walter Benjamin und Antonio Gramsci / Politicization Between the Lines: Remarks on the Agitational Character of Walter Benjamin’s and Antonio Gramsci’s Wr - Schmidt, Matthias (International Gramsci Journal, 2023)
The writings of Walter Benjamin and Antonio Gramsci have often been compared with each other because of their similar appearance and their seemingly analogous methods. Both authors’ corpora challenge the idea of linear writing and can rather be described as fragmentary, rhizomatic networks which keep developing their ideas and notions with every reader trying to synthesize their elements. This article examines these typical modes of writing regarding their specific political impact on their readers. I will therefore reconstruct Benjamin’s and Gramsci’s understanding of the political intellectual, in order to subsequently contrast the functional structure of their texts. While Benjamin’s approach to montage prompted him to make political use of irritating ellipses, Gramsci’s approach aimed at gradually sharpening the notions developed, to broaden the philosophical basis of a common political consciousness.